LITERATURE REVIEW : FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA INDUSTRI - Meisi Riana (Universitas Quality, 2021)
Personal protective equipment is part of the prevention of accidents and occupational diseases. Seeing that the benefits of PPE are very important for workers, it is necessary to review the behavior of workers using PPE in industry. The purpose of this study is to look at the factors that influence workers in using PPE, which later results from the analysis can be used as a basis and reference for academics and practitioners in the application of occupational health and safety culture in industry, especially in the use of PPE. The research method used is Literature Review, data collection is carried out by internet searches through Google Scholar, Researchgate, and ProQuest with the keywords Personal Protective Equipment, PPE, Industry, PPE, and industrial. The articles used are articles in the 2016-2020 timeframe. The initial search results for articles found 1,432 but after screening based on predetermined inclusion criteria, 15 articles were selected consisting of 13 Indonesian articles and 2 international articles. The conclusion obtained in this study is that there are several factors that influence the behavior of workers in using PPE, namely predisposing factors between other attitudes, knowledge, and comfort in using PPE. Driving factors include training, supervision, and policies or regulations. Supporting factors include social support and the completeness of the PPE used.